An Enolate‐Mediated Organocatalytic Azide–Ketone [3+2]‐Cycloaddition Reaction: Regioselective High‐Yielding Synthesis of Fully Decorated 1, 2, 3‐Triazoles. Issue 51 (3rd November 2014) - Shashank, Adluri B.; Karthik, S.; Madhavachary, R.; Ramachary, Dhevalapally B.
Abstract An enolate‐mediated organocatalytic azide–ketone [3+2]‐cycloaddition (OrgAKC) reaction of a variety of enolizable arylacetones and deoxybenzoins with aryl azides was developed for the synthesis of fully decorated 1, 4‐diaryl‐5‐methyl(alkyl)‐1, 2, 3‐triazoles in excellent yields with high regioselectivity at 25 °C for 0.5–6 h. This reaction has an excellent outcome with reference to reaction rate, yield, regioselectivity, operation simplicity, and availability of substrates and catalyst. This reaction has advantages over the previously known metal‐mediated reactions.